2014
DOI: 10.1146/annurev-orgpsych-031413-091244
|View full text |Cite
|
Sign up to set email alerts
|

The Story of Why We Stay: A Review of Job Embeddedness

Abstract: In this article, we examine the history and development of job embeddedness, beginning with the story of the idea's conception, theoretical foundation, and original empirical structure as a major predictor of employee voluntary turnover. We then consider more recent expansions in the theoretical structure and empirical measurement of job embeddedness, exploring job embeddedness as a causal indicator model versus a reflective model. Next, we review some promising expansions of embeddedness to new domains (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(156 citation statements)
references
References 45 publications
3
146
0
7
Order By: Relevance
“…This may partly be a function of limited relative studies available, such as embeddedness (i.e., a possible Type II error), but it also points to an interesting consideration: Possibly, who leaves (i.e., a "bad apple" versus a supportive colleague) is more important than the raw metric of how many employees leave. In job embeddedness theory, considering the quality of links-beyond mere quantity-could be insightful in this regard (Lee, Burch, & Mitchell, 2014). In general, though the results show that when the work environment is one in which withdrawal, thoughts of withdrawal, and actual quitting are higher, antecedents such as alternatives, search, and withdrawal cognitions have even more positive effects, whereas factors that typically prevent turnover (e.g., high performance, longer tenure and higher pay) have weaker (i.e., closer to zero) effects.…”
Section: Resultsmentioning
confidence: 99%
“…This may partly be a function of limited relative studies available, such as embeddedness (i.e., a possible Type II error), but it also points to an interesting consideration: Possibly, who leaves (i.e., a "bad apple" versus a supportive colleague) is more important than the raw metric of how many employees leave. In job embeddedness theory, considering the quality of links-beyond mere quantity-could be insightful in this regard (Lee, Burch, & Mitchell, 2014). In general, though the results show that when the work environment is one in which withdrawal, thoughts of withdrawal, and actual quitting are higher, antecedents such as alternatives, search, and withdrawal cognitions have even more positive effects, whereas factors that typically prevent turnover (e.g., high performance, longer tenure and higher pay) have weaker (i.e., closer to zero) effects.…”
Section: Resultsmentioning
confidence: 99%
“…Future research could test the predictive value of models including these factors in addition to those that were already studied in our current model (Bakker & Demerouti, 2017;Van der Heijden et al, 2018). Research may also pay attention to age-related differences in the workplace (Fasbender & Wang, 2017a,b) Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Given the usefulness of job embeddedness in retaining employees, researchers have made considerable efforts to explore its antecedents, including organisational factors (e.g., benefit programmes and human resource management practices) and personal characteristics (e.g., extraversion and enhanced and newly acquired skills; Ghosh & Gurunathan, 2015). Although social relations in the workplace have been recognised as a driving force for job embeddedness (Mitchell, Holtom, Lee, Sablynski, & Erez, 2001), they have received relatively little empirical attention (Lee, Burch, & Mitchell, 2014). Existing work has shown that low levels of co-worker job embeddedness lead to high levels of co-worker job search behaviour, which in turn lead to employee turnover (Felps et al, 2009), and supervisor job embeddedness relates positively to employees' own job embeddedness (Ng & Feldman, 2013).…”
mentioning
confidence: 99%